2004
DOI: 10.1016/j.ejvs.2003.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Multi-layer Compression: Comparison of Four Different Four-layer Bandage Systems Applied to the Leg

Abstract: When a bandage is applied as part of a multi-layered system it exerts approximately 70% of the pressure exerted when applied alone, thus challenging the commonly-held assumption that the final pressure achieved by a multi-layer bandaging system is the sum of the pressures exerted by each individual layer. Each of the four bandaging systems exerted different final pressures and gradients and different changes with posture change. These differences have important implications, which could influence the selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 9 publications
0
30
0
2
Order By: Relevance
“…In the study by Ruckley et al [15] it was found that each of four sets of four-layer compression systems (Profore ® , Ultra Four ® , K-Four ® and System 4 ® ) regardless of similar physical properties generated charac­teristically different pressures. This concerned each of the bandage layers as well as the cumulative value generated by the whole system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Ruckley et al [15] it was found that each of four sets of four-layer compression systems (Profore ® , Ultra Four ® , K-Four ® and System 4 ® ) regardless of similar physical properties generated charac­teristically different pressures. This concerned each of the bandage layers as well as the cumulative value generated by the whole system.…”
Section: Discussionmentioning
confidence: 99%
“…Materials which are not elastic (short-stretch), although they do not demand frequent replacements and they can be left on a limb for several days, lose their primal tension very quickly and they cause the decrease of pressure under a dressing. However, the advantage of short-stretch materials is the ability to generate high active pressures and prevention of limb swelling while oedema occurs [14, 15]. Blair et al .…”
Section: Introductionmentioning
confidence: 99%
“…Now using Figure 3, the pressures produced by other layers of the bandage are calculated to be P 2 ≈ 0.985 × P 1 = 5.75 mmHg P 3 ≈ 0.97 × P 1 = 5.66 mmHg P 4 ≈ 0.955 × P 1 = 5.58 mmHg Hence, the interface pressure at the mid-calf level is calculated to be P ≈ P 1 + P 2 + P 3 + P 4 = 22.83 mmHg Comparison of the above values to values predicted by the simple multiplication method shows that the simple multiplication method will overestimate the pressure by 3.5% for the ankle region and 2.32% for the mid-calf level. Table 4 are based on the assumption that the pressure measurement device used by Dale et al 11 is reliable and accurate. In addition, it should be emphasized that the tension values that were calculated for the natural padding bandage 'Ex 1' are believed to be high and inaccurate.…”
Section: Results and Analysismentioning
confidence: 99%
“…The results reported above are close to the ones published by Dale et al 11 They found that the difference in the percentage between the pressure produced by the cohesive layer as part of the four-component system compared with the pressure produced when it is applied alone is about 73.2%. 11 The difference between the theoretical calculation and the experimental work is likely to be because the values quoted are for mean values over six points of measurement for four multicomponent systems applied by four bandagers. 11 In addition, the above calculation assumed that all bandage components are 1.3 mm in thickness, while components of commercial multicomponent MCB differ in their thicknesses and some are thicker than 1.3 mm.…”
Section: Discussionmentioning
confidence: 98%
“…In most cases the interface pressure, effectively the compression dose, is not accurately known and is likely to be different from the ideal graduated compression intended on application. 7,8 Furthermore, as the dimensions of the affected limb change under the influence of external compression, the interface pressure changes (REF). 1 Variability in the application and sustainability of interface pressure is likely to lead to variable clinical efficacy, for example, healing rates. Indeed, the healing rates reported for VLU vary considerably.…”
Section: Introductionmentioning
confidence: 99%